PREGNANCIES WITH PULMONARY HYPERTENSION SECONDARY TO CONGENITAL HEART DISEASE - Kaluarachchi, A; De Alwis, D; Gnanasekaram, R; Gunawansa, N; Wijerathne, C N; Seneviratne, H R (My University, 2012)
Introduction: Heart disease complicating pregnancy is a significant cause of maternal morbidity and mortality. Pulmonary hypertension (PHT) secondary to congenital heart disease (CHD ) is potentially a fatal condition. Objectives : To find the maternal and foetal outcome of pregnancies complicated with PH T secondary to congenital heart disease. Study Design : Retrospective descriptive study. Setting: University Obstetric Unit, De Soysa Hospital for Women, Colombo. Method : Data collected from the records of 77- consecutive mothers with congenital heart disease who delivered during the period from 01/09/98 to 30/11/ 00. Results: This study group consisted 77 mothers with CHD , their mean age=27.94yr (SD±5.22yr) and their mean parity was 1.58(SD+0.75). 41.6% (n=32) had Mitral Valve Prolapse, 33.7% (n=26) had Atrial Septal Defect (ASD) and 16.9% (n=13) had Ventricular Septal Defect (VSD). 18.4%(n=14) had PH T and 10 of them were in their 1 pregnancy. A S D was the primary lesion in 10 and VS D in 4. 16 put of 26 AS D patients and all VS D patients did not have corrective surgery done. None of the patients with PH T had undergone corrective surgery. The only two maternal deaths and two perinatal deaths were seen in the group with PHT. Conclusion : Despite the advancement of the health care services pregnancies complicated with PH T is not uncommon. Early surgical correction of congenital heart lesions and counseling of women of reproductive age group with PH T against pregnancy are two areas need addressing.